2010
DOI: 10.1590/s0100-40422010000700007
|View full text |Cite
|
Sign up to set email alerts
|

Influência da temperatura, umidade e profundidade do solo na persistência do diurom e sulfato de endossulfam em um solo tropical

Abstract: Recebido em 3/9/09; aceito em 6/4/10; publicado na web em 20/7/10 INFLUENCE OF TEMPERATURE, SOIL HUMIDITY AND SOIL DEPTH ON THE PERSISTENCE OF DIURON AND ENDOSULFAN SULFATE IN A TROPICAL SOIL. The influence of temperature (30 and 40 ºC) and soil humidity (20, 50 and 70% of water holding capacity) on the degradation of the herbicide diurom and the endosulfan metabolite, endosulfan sulfate was studied under laboratory conditions, in different soil layers (0-30, 30-38 and 38-83 cm) of an Oxisol (Yellow Latosol) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
2
0
5
Order By: Relevance
“…Assim, observa-se uma degradação mais rápida do metabólito sulfato de endossulfam na camada mais profunda do solo (50-70 cm). Silva et al (2010) avaliaram a influência da umidade, temperatura e profundidade do solo na degradação do sulfato de endossulfam em solos incubados provenientes de uma região agrícola de Mato Grosso e observaram valores de TD 50 entre 6 a 88 dias. A degradação mais rápida de sulfato de endossulfam na camada mais profunda do solo, conforme constatado neste estudo, também foi observada por Silva et al (2010).…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Assim, observa-se uma degradação mais rápida do metabólito sulfato de endossulfam na camada mais profunda do solo (50-70 cm). Silva et al (2010) avaliaram a influência da umidade, temperatura e profundidade do solo na degradação do sulfato de endossulfam em solos incubados provenientes de uma região agrícola de Mato Grosso e observaram valores de TD 50 entre 6 a 88 dias. A degradação mais rápida de sulfato de endossulfam na camada mais profunda do solo, conforme constatado neste estudo, também foi observada por Silva et al (2010).…”
Section: Methodsunclassified
“…Silva et al (2010) avaliaram a influência da umidade, temperatura e profundidade do solo na degradação do sulfato de endossulfam em solos incubados provenientes de uma região agrícola de Mato Grosso e observaram valores de TD 50 entre 6 a 88 dias. A degradação mais rápida de sulfato de endossulfam na camada mais profunda do solo, conforme constatado neste estudo, também foi observada por Silva et al (2010). É provável que esta degradação mais rápida na camada mais profunda do solo tenha sido favorecida pelo maior teor de argila quando comparada com a superfície, o que pode favorecer o processo denominado hidrólise catalisada pela argila (Awasthi & Prakash, 1997).…”
Section: Methodsunclassified
“…Silva et al (2010) found an efficient degradation of contaminants in deeper soil layers due to the increased amount of clay in depth. Bitton (1994) noted that in layers deeper than 3 m in the soil profile, fecal coliforms present in wastewater cannot survive, probably due to the lack of organic material, which has fundamental importance for their survival.…”
Section: Sustainability Classes For Final Waste Disposalmentioning
confidence: 94%
“…Moreover, endosulfan sulfate is more persistent than its parental isomers. 38 Other authors also found these compounds on groundwater, such as Dalton and Frick 39 who evaluated the evolution of pesticides concentrations from 1993 to 2005 in aquifers in Florida, USA. Atrazine, DEA, metolachlor, alachlor, fluometuron and tebutiuron were detected in 20% of the samples with the metabolite desethylatrazine showing an increase in concentration on the Florida Aquifer during the study period.…”
Section: Pesticides On Groundwatermentioning
confidence: 98%